A comparative life cycle assessment of structural flooring systems in Western Australia. (March 2021) - Hahnel, Grace; Whyte, Andrew; Biswas, Wahidul K.
Abstract: The construction industry has the potential to address negative impact on the environment by considered use of scarce natural resources, through a more informed choice of fit-for-purpose building materials. This paper presents a holistic life-cycle assessment (LCA) to facilitate the selection of environmentally friendly designs. Building on previous studies suggesting that engineers can reduce their environmental impact through conscious material selections and a substitution of traditional specifications, this work presents a case-study related to structural flooring systems in which a LCA approach for selecting the environmentally benign option, complements structural integrity design decisions. This study examined the life cycle environmental impacts associated with timber, steel and concrete structural flooring systems' options, for WA. ISO14040-44 guidelines were followed to carry out this 'cradle to cradle' LCA approach for calculating respective impacts. The comparisons of options using local benchmarks concluded that timber has the lowest environmental impacts followed by steel, and then 'GreenStar' concrete, with eco-classifications assessing the environmental impact of each flooring system for Perth WA across key environmental impacts categories and individual life cycle stages. This showed local hotspots in environmental categories of fossil fuel depletion and climate change and life cycle stages of mining to manufacture, construction and building operation. This research provides the reflection on what makes a sustainable design and, by targeting feasible solutions for WA, and by presenting the findings of a somewhat complex LCA analyses as a singular easy-to-use value, which addresses the need for enhanced materials awareness. Highlights: A holistic life-cycle assessment has been used to facilitate the selection of environmentally friendly flooring systems. Timber flooring system has the lowest environmental impacts followed by steel, and then 'GreenStar' concrete. Fossil fuel depletion and climate change were found to be the predominant impacts.